Scaling-Up Performance-Based Financing in Burkina Faso: From PBF to User Fees Exemption Strategic Purchasing - Mathieu Seppey; Valéry Ridde; Paul-André Somé (International Journal of Health Policy and Management, 2022)
BackgroundNumerous countries have undertaken performance-based financing (PBF) reforms to improve quality and quantity of healthcare services. However, only few reforms have successfully managed to achieve the different scale-up phases. In Burkina Faso, a pilot project was implemented, but was put on hold before being scaled. During the writing of this article, discussions to scale-up were still ongoing on a national strategic purchasing strategy within a government led user fee exemption policy. MethodsThis study’s objective is to identify facilitators and barriers to scaling-up for that pilot, based on the World Health Organization’s (WHO’s) theoretical framework. Interviews were conducted in three health centres and in Ouagadougou to discuss the scale-up with different actors. The software QDA Miner© was used to help in the framework analysis. ResultsThe low involvement of some key stakeholders (mainly decision-makers) and the unstable context hindered ownership of the project, thus its priority on the political agenda. PBF reform therefore lost its momentum to the benefit of a user fee exemption policy. This latter program was seen to be more beneficial since it addressed access to healthcare services, in comparison to service quality, which was the PBF’s relative advantage. A scale-up of some PBF elements (eg, strategic purchasing tools) is however still in discussion in 2019, but would be integrated within the user fee exemption program. Increased costs during the PBF’s implementation gave the impression that the project was too costly and not scalable. The involvement of an important funding agency (World Bank, WB) also fed the impression of high costs, which demotivated the actors, especially decision-makers. ConclusionContextual factors remain central to the implementation of PBF, while their evaluation and mitigation have remained unclear. The participation of key actors in scaling-up operations and the use of social science as tools to better understand the context is therefore primordial.